Renewable Energy Benefits Leveraging Local Capacity for Solar Water Heaters - IRENA, International Renewable Energy Agency (eBook Partnership, 2022)
This report aims to expand policy makers' understanding of the steps needed to develop a local market for solar water heaters, and the existing capabilities that can be leveraged to do so. The report also highlights opportunities to create local value by setting up a domestic industry around solar water heaters.